The effectiveness of scratch interactive media in mathematics learning: A literature review study - Indah Febi Azhari; Olivia Octavianti (IKIP Siliwangi, 2026)
This research aims to systematically review the specific effectiveness of utilizing Scratch interactive media in enhancing the quality of mathematics learning processes. This improvement in quality is examined through its impact on student learning outcomes and interactive experiences.The methodology employed is a Systematic Literature Review (SLR). This process was designed to comprehensively identify, critically evaluate, and interpret all available empirical evidence concerning the effectiveness of mathematics learning media that leverage Scratch. The initial search procedure successfully gathered a total of 40 articles from various trusted scientific databases. The studies considered were restricted to publications released within the timeframe of 2020 to 2025. After undergoing a rigorous screening process—applying predefined inclusion and exclusion criteria based on topic relevance and study methodology—it was determined that 21 eligible articles were selected for in-depth analysis. This analysis focused on both the quantitative and qualitative results regarding Scratch's effectiveness. The findings from the systematic review consistently indicate that the use of Scratch provides a significant impact on improving the quality of mathematics learning. Specifically, Scratch successfully transforms the learning process into one that is more interactive and engaging, which, in turn, effectively enhances students' cognitive abilities, including conceptual understanding and problem-solving skills. These results affirm Scratch as a valid and effective pedagogical innovation with great potential for wider integration into the mathematics curriculum in the digital age.